A critical analysis of corruption and anti-corruption policies in Italy. Issue 2 (28th March 2020) - Maggio, Paola
Abstract : Purpose: This study aims to critically analyse the Law 9 January 2019, n. 3, on "Measures to fight crimes against the public administration and on the transparency of political parties and movements" (so-called bribe-destroyer law). Design/methodology/approach: This paper draws on reports, legal scholarship and other open-source data to examine a legislative innovation for the corruption in Italy in relation to the general guarantees of the trial process and with the controversial paradigm of the national perception index of bribery. Findings: The Italian legislative initiative that will be examined is innovative in nature and goes beyond the constitutional and conventional principles on procedural guarantees. The new initiative needs to be integrated into the international and European action against bribery that targets criminal proceeds, and at the same time, be anchored in respect for human rights during the process. Research limitations/implications: The new initiative needs to be integrated into the international and European action against bribery that targets criminal proceeds, and at the same time, be anchored in respect for human rights during the process. Practical implications: Despite the aggressiveness and lofty proclamations by those who aspire to fight corruption from the highest levels, the goal of rehabilitating Italy from one of the seven "deadly sins" that delay economic growth still seems far off. Social implications: In the absence of public ethics, the increase in criminalisation does not seem sufficient on its own to guarantee the containment of the phenomenon. Originality/value: This study examines the strengths and weaknesses of the important new law, its compatibility with human rights standards and its relationship to international standards of anti-bribery policies. The aggressive legislation critically relies on the pervasive and persistent lack of perception of corruption as a crime. In the confiscation (and now also reparation) of equivalent that normally addresses assets accumulated in a lawful manner, the periculum is even presumed in re ipsa and the classical aims of caution undergo a total torsion revealing an authoritarian face that takes on the meaning of anticipating further sanctioning contents. Finally, the presence of many levels of sanctioning in relation to the same fact poses serious problems of violation of the ne bis in idem rule.